A research study of the concealed wisdom in the Philosophy of migration - Shabana Noreen; Maryam Noreen (jihat-ul-islam, 2021)
Emigration is an unforgettable event in the history of Islam and a great Da'wah stage. Undoubtedly, migration has played an important role in the expansion and promotion of the Islamic of the Holy Prophet. Migration is one of the practical measures taken by the Prophet to carry out the Islamic Revolution and reach his goal. The greatest sacrifice of his followers for a cause is to leave his home, relatives, farm, business, relationships, and all relationships for him and to meet this test. No group can win the Certificate of Loyalty and the Medal of Faith without going through that ordeal. This ordeal is the migration from the beloved homeland of Dar al-Kufr to a foreign land for the security of faith for the sake of its mission, the reward of which is Paradise.